Perbedaan Penurunan Kadar Total Suspended Solid Dengan Metode Sedimentasi Dan Koagulan Pada Limbah Cair Peternakan Babi Tahun 2021 - I Gusti Made Surya Adnyana; I Wayan Sali; Anysiah Elly Yulianti (Poltekkes Kemenkes Denpasar, 2022)
Liquid waste as the results of pig farm business should meet the requirements of physical parameters before being discharged into the bodies of water, one of which is the Total Suspended Solid (TSS) parameter. The results of the TSS levels examination from the liquid waste of the pig farm business exceeded the predetermined limit, which is an average of 1,112 mg/L. One of the liquid waste treatment methods to reduce TSS levels is sedimentation and coagulant methods. This research was conducted by giving PAC as much as 0.5 g/L in each treatment with time variations for 20 minutes, 40 minutes and 60 minutes. This research was conducted with three replications and each replication using a duplo system for two repetitions. This type of research is a true experiment with a Pre test – Post test Control Group Design. The results were decreased by 20 minutes by 142 mg/L, 40 minutes by 98 mg/L and 60 minutes by 90 mg/L. Based on the results of the One Way test ANOVA obtained a Sig. p 0,000 (α 0,05) which means H0 is rejected and Ha is accepted, meaning there is a difference in TSS levels between control, 20 minutes, 40 minutes and 60 minutes which means significance. The conclusion of this study shows that treatment with a sedimentation time of 60 minutes is the most effective time to reduce TSS levels of pig farm’s liquid waste.